Pharmacokinetics of (synthetic) cannabinoids in pigs and their relevance for clinical and forensic toxicology. (24th June 2016) - Schaefer, Nadine; Wojtyniak, Jan-Georg; Kettner, Mattias; Schlote, Julia; Laschke, Matthias W.; Ewald, Andreas H.; Lehr, Thorsten; Menger, Michael D.; Maurer, Hans H.; Schmidt, Peter H.
Graphical abstract: Highlights: First study on the pharmacokinetics of JWH-210 and RCS-4 in pigs. A three-compartment model described best pharmacokinetic data of THC, JWH-210, and RCS-4. The allometrically upscaled THC pig model resulted in successful prediction of human exposure. Pigs useful for prediction of human pharmacokinetics of synthetic cannabinoids. Abstract: Synthetic cannabinoids (SCs) are gaining increasing importance in clinical and forensic toxicology. They are consumed without any preclinical safety studies. Thus, controlled human pharmacokinetic (PK) studies are not allowed, although being relevant for interpretation of analytical results in cases of misuse or poisoning. As alternative, in a controlled animal experiment, six pigs per drug received a single intravenous dose of 200 μg/kg BW each of Δ 9 -tetrahydrocannabinol (THC), 4-ethylnaphthalen-1-yl-(1-pentylindol-3-yl)methanone (JWH-210), or 2-(4-methoxyphenyl)-1-(1-pentyl-indol-3-yl)methanone (RCS-4). In addition, six pigs received a combination of the three drugs with the identical dose each. The drugs were determined in serum using LC–MS/MS. A population (pop) PK analysis revealed that a three-compartment model described best the PK data of all three cannabinoids. Central volumes of distribution were estimated at 0.29 L/kg, 0.20 L/kg, and 0.67 L/kg for THC, JWH-210, and RCS-4, respectively. Clearances were 0.042 L/min/kg, 0.048 L/min/kg, and 0.093 L/min/kg for THC, JWH-210, and RCS-4, respectively. The popPK THC pig model was upscaled to humans using allometric techniques. Comparison with published human data revealed that the concentration-time profiles could successfully be predicted. These findings indicate that pigs in conjunction with PK modeling technique may serve as a tool for prediction of human PK of SCs.